2016
DOI: 10.3109/00498254.2016.1144229
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics andN-acetylation metabolism ofS-methyl-l-cysteine andtrans-S-1-propenyl-l-cysteine in rats and dogs

Abstract: 1. Pharmacokinetics and N-acetylation metabolism of S-methyl-L-cysteine (SMC) and trans-S-1-propenyl-L-cysteine (S1PC) were examined in rats and dogs. SMC and S1PC (2-5 mg/kg) were well absorbed in both species with high bioavailability (88-100%). 2. SMC and S1PC were excreted only to a small extent in the urine of rats and dogs. The small renal clearance values (<0.03 l/h/kg) indicated the extensive renal reabsorption of SMC and S1PC, which potentially contributed to their long elimination half-lives (>5 h) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 17 publications
0
23
0
Order By: Relevance
“…Brie y, raw garlic (Allium sativum L.) was sliced into pieces, which was followed by immersing in ethanol 20-50% (v/v) and aging for more than 10 months at room temperature. S1PC, SAC and SAMC were synthesized according to the previous methods [41,42], and the purity was >99.0%.…”
Section: Methodsmentioning
confidence: 99%
“…Brie y, raw garlic (Allium sativum L.) was sliced into pieces, which was followed by immersing in ethanol 20-50% (v/v) and aging for more than 10 months at room temperature. S1PC, SAC and SAMC were synthesized according to the previous methods [41,42], and the purity was >99.0%.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous in vitro metabolic study also demonstrated that there was a species difference in the N-acetylation metabolism of SAC, SMC, and S1PC between animals and humans, suggesting that in humans, N-acetylated metabolites are formed to a lesser extent. 18,19) Taken together, it is unlikely that the N-acetylated metabolites of SAC, SMC, and S1PC cause DDI due to CYP inhibition in humans. We also evaluated the effects of the minor metabolites (NAc-SACS, NAc-SMCS, NAc-S1PCS) on the activities of CYP isoforms and found that all the compounds had little influence on the five isoformmediated metabolisms (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…30) In any case, SAC and SMC are very unlikely to inhibit CYP3A4 activity in vivo; a preliminary pharmacokinetic study of AGE demonstrated that the maximum plasma concentration of SAC was 140 nM, 31) which is lower by three orders of magnitude than the concentration (0.1 mM) used by Greenblatt et al 17) Recently, we examined the metabolism and pharmacokinetics of SAC, SMC, and S1PC in rats and dogs and found that these compounds undergo N-acetylation and S-oxidation metabolism. 18,19) In both species, the N-acetylation is the major metabolic pathway to eliminate SAC and S1PC. In contrast, SMC is metabolized to NAc-SMC only to a small extent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AGE has been shown to exert immuno-enhancing and anti-inflammatory effects (1)(2)(3)(4)(5). S-1-propenylcysteine (S1PC), a major characteristic sulfur compound in AGE, which exhibits good oral bioavailability in rats and canines (6), has been shown to exert several beneficial effects, such as immunoregulatory, anti-hypertensive and blood flow-promoting effects (7)(8)(9)(10). Moreover, in our previous recent studies, it was indicated that S1PC promoted intestinal immunoglobulin A (IgA) production and inhibited lipopolysaccharide (LPS)-induced IL-6 production (7,10).…”
Section: Introductionmentioning
confidence: 99%